2003
DOI: 10.1139/x03-055
|View full text |Cite
|
Sign up to set email alerts
|

Stand structure governs the crown collisions of lodgepole pine

Abstract: We investigated tree sway and crown collision behavior of even-aged lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) stands of different structure in Alberta, Canada, to examine how these factors might affect loss of leaf area as stands mature. The Two Creeks stand (TC) had high density and slender trees, while the Chickadee stand (CH) had stout trees. The TC stand was then thinned (TCT) to reduce the stand density. For each stand, simultaneous tree sways of a group of 10 trees were monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 27 publications
4
70
0
2
Order By: Relevance
“…This supports the idea that increased wind exposure and bending may damage the xylem of tree stems, reducing hydraulic conductivity and intensifying moisture stress (Fredericksen et al 1994, Liu et al 2003. Bending and damage to water-conduct- ing tissue is potentially a greater problem for more slender stems due to wider oscillations of the crowns than for trees with stout boles (Rudnicki et al 2003).…”
Section: Discussionsupporting
confidence: 70%
“…This supports the idea that increased wind exposure and bending may damage the xylem of tree stems, reducing hydraulic conductivity and intensifying moisture stress (Fredericksen et al 1994, Liu et al 2003. Bending and damage to water-conduct- ing tissue is potentially a greater problem for more slender stems due to wider oscillations of the crowns than for trees with stout boles (Rudnicki et al 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Trees growing in a crowded stand or trees with larger crowns may experience more physical interactions with neighboring trees, resulting in increased crown recession (Power et al 2012). Crowns of tall trees are also subject to considerable movement due to wind-blow and resulting collisions may lead to substantial abrasion of branches and foliage (Rudnicki et al 2003). Any change in the HCB may also reflect variability in the epicormic re-sprouting after a canopy loss during a drought period and after snow damages (Taylor et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ex Loud. ), a closely related species with similar stand development that is capable of hybridizing with P. banksiana, have shown that trees collide hundreds of times per hour in moderate winds (Rudnicki et al 2003), that preventing these collisions increases leaf area (Meng et al 2006), and that trees do not compensate for leaf area lost to collisions by maintaining longer crowns (Fish et al 2006). We suggest that the impact of collisions may be asymmetric: smaller trees are disproportionately damaged when they collide with large trees because the upper branches (which are more important for intercepting light) of shorter trees collide with lower branches (which are less important for intercepting light) of the taller trees.…”
Section: Discussionmentioning
confidence: 99%